Seagrass Potential as Supporting Ecotourism in Sibu Island, Subdistrict North Oba, North Maluku Province - Salim Abubakar; Riyadi Subur; Rina Rina; Masykhur Abdul Kadir; Mesrawaty Sabar; Darmawaty Darmawaty; Nebuchadnezzar Akbar (Sangia Publishing, 2020)
Seagrass Ecotourism is a tourism activities based on the ecosystem of seagrass. Component of seagrass consist of vegetation and biota that associated with the seagrass. The purpose of this research is to understand the condition biophysics of seagrass (Types of seagrass, Cover of seagrass, fish, makrozoobenthos, types of substrat, water brightness, the depth of the seagrass) and to establish the suitability of seagrass to support nautical ecotourism. This research have been done in Sibu island, Guraping village, north oba district, Tidore city for 6 month from April – September 2020. The method that used is a survey method consist of direct measuring of types seagrass, cover of seagrass, fish, makrozoobenthos, types of substrat, water brightness, the depth of the seagrass. The data analysis includes percentage of cover seagrass and the suitability index of seagrass ecotourism. The result of the biophysical study were obtained are 8 types of seagrass, cover of seagrass (51,04- 92,71%), fish (12 types), makrozoobenthos (17 types), brightness (77-100%), substart (sand, muddy sand, mud) flow speed (0,01- 0,06 m/dt) and the depth of the seagrass (1-2,5 m). Sibu island could be developed as a region of Seagrass Ecotourism with index suitability tourism (IKW) station 1,3,4 and for the whole are located in category S1 (very suitable) and station 2 is in the suitable category.